2010
DOI: 10.1007/s00330-010-1979-0
|View full text |Cite
|
Sign up to set email alerts
|

CT predictors of mortality in pathology confirmed ARDS

Abstract: Our study suggests that >80% of lung involvement, RA/LA ratio >1, and varicoid bronchiectasis predict mortality in patients with ARDS/DAD. Signs of right-sided heart failure (PA dilation greater than 3 cm and RV/LV ratio greater than 0.9) approached significance. CT findings did not differentiate DAD from DAD-OP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
3
46
1
1
Order By: Relevance
“…In line with our findings, Chung et al 6 found that parenchymal involvement of Ͼ80% shown on CT scans of subjects with ARDS was associated with high mortality. The study by Chung et al 6 defining CT predictors of mortality in subjects with ARDS also demonstrated that a ratio of right to left atrial diameter of Ͼ1 was significantly more common in non-survivors than in survivors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our findings, Chung et al 6 found that parenchymal involvement of Ͼ80% shown on CT scans of subjects with ARDS was associated with high mortality. The study by Chung et al 6 defining CT predictors of mortality in subjects with ARDS also demonstrated that a ratio of right to left atrial diameter of Ͼ1 was significantly more common in non-survivors than in survivors.…”
Section: Discussionsupporting
confidence: 93%
“…16 The percentage of lung involvement was estimated qualitatively to the nearest 10th percentile (eg, 10%, 20%) by evaluating the axial and coronal CT images. 6 The radiologist suggested a specific etiology when a characteristic pattern was identified on CT scans.…”
Section: Evaluation Of Lung Parenchymamentioning
confidence: 99%
See 1 more Smart Citation
“…19 The presence of traction bronchiectasis was also found to be a predictor of poor outcome in another study, along with disease affecting over 80% of the lungs, and signs of elevated right heart pressure (pulmonary artery dilatation and an enlarged right ventricle). 20 This study also suggested that patients who have a pure consolidative pattern of disease in the early stages have a better chance of survival. The implication of this observation is that, because consolidation is not a marker of fibrotic change, there is a more favorable outcome for this group of patients, thus indirectly supporting the finding that early fibrosis in ARDS is associated with a higher risk of death.…”
Section: Ct As a Means Of Prognosticating In Ardsmentioning
confidence: 76%
“…Despite this fact, the development of bronchiectasis, in particular, is a poor prognostic sign. In the study by Chung and colleagues, 32 the development of varcoid bronchiectasis was associated with higher mortality, seen in 43% of patients who died but only 7% of survivors.…”
Section: The Subacute To Chronic Appearance Of Acute Lung Injurymentioning
confidence: 93%